História evolutiva de Leopardus colocolo (Mammalia, Felidae): análise de padrões filogeográficos e sua influência no processo de hibridação com Leopardus tigrinus - Santos, Anelisie da Silva (2012)
The pampas cat, Leopardus colocolo, is a little-known species of Neotropical felid that has a broad geographic distribution in South America, and is strongly associated with grasslands. The presence of phenotypic differences among geographic populations of this species has raised questions about the demographic history and taxonomy of this felid. More recently, initial phylogeographic studies showed that this species indeed possesses a strong genetic structure, but were mostly restricted to Andean samples, so that much of its distribution was not analyzed in detail. Furthermore, the recent discovery of evidence of hybridization between L. colocolo and another Neotropical felid (L. tigrinus) in central and northeastern Brazil, added an even greater complexity to the evolutionary history of this species, and emphasized the need for more detailed studies on its phylogeographic patterns and historical demography. Previous studies have indicated that this hybridization event is relatively old, and is currently detected only as an introgression of L. colocolo mitochondrial DNA (mtDNA) into L. tigrinus populations, without any trace so far identified in the nuclear genome. Therefore, the aim of this study was to analyze four mitochondrial segments in L. colocolo individuals sampled broadly across their geographic distribution, along with samples of L. tigrinus hybrids from central and northeastern Brazil. The analysis of 2,141 base pairs of the mtDNA control region and ATP8, ND5 and Cyt-b genes revealed a strong population structure in L. colocolo, with high haplotype and nucleotide diversity in comparison with others Neotropical cats. Haplotypes from Chile, Bolivia and Argentina were positioned as the most basal in the phylogeographic structure of L. colocolo, while samples from Brazil and Uruguay formed recent, internal groups, suggesting a west-to-east colonization for this species. Demographic analyses indicated the occurrence of two episodes of population expansion, an earlier one (ca. 200,000 years ago) in the west, and another ca. 50,000 years ago in the east. The latter coincides with paleoclimatic and paleogeographic studies that indicated an expansion of grasslands in Brazil and consequent loss of forests. The joint analysis with the L. tigrinus hybrid samples revealed a complex history of hybridization. We found no haplotype sharing between L. colocolo and L. tigrinus hybrids, supporting the hypothesis that this hybridization event is quite old. Moreover, the analysis of population structure revealed that the pampas cat populations from southern Brazil and Uruguay are phylogenetically closer to L. tigrinus hybrid haplotypes than to the extant lineages of L. colocolo from central and northeastern Brazil. The most plausible interpretation to this unusual pattern is that ancestral L. colocolo haplotype lineages from central Brazil have only been sampled in present-day hybrids, and may be extinct in their original species. The observed pattern also indicates that southern Brazil and Uruguay were colonized by L. colocolo from central Brazil, with no immediate connection to nearby populations still present in Argentina. This has direct consequences for the conservation of this group, which is geographically isolated and appears to evolve without gene flow (at least mitochondrial) with nearby populations. If this result is confirmed with nuclear markers, it will emphasize the immediate prioritization of these populations for conservation and management. From an evolutionary standpoint, our results showed the importance of analyzing L. colocolo populations from eastern South America, as well as the inclusion of L. tigrinus hybrids, because an essential portion of the pampas cat mitochondrial history seems to be currently recorded only by these introgressed haplotypes.